Dog man mothering heights - Pilkey, Dav; Pilkey, Dav (New York Scholastic / Graphix, 2021)
"In the 10th graphic novel in Dav Pilkey's Dog Man series, Petey confronts his past and memories of his mother"--
Comic Strips
Ages 7 and Up
Grades 2-3
Keywords: Picture stories